Resiliensi di LKSA: Perceived Social Support dan Problem Focused Coping pada Remaja - Meidina Dwi Putri; Hari Setyowibowo; Fredrick Dermawan Purba (Psyche 165 Journal, 2022)
Adolescence who live in orphanages faced adversity in their life who are different from adolescence in general. They are required to be able to overcome the problems on their own without parents. The inability to overcome these problems can increase the risk of stress and prone to emotional problems. This study aims to determine the relationship between perceived social support and problem-focused coping on the level of resilience of adolescence in Bandung orphanages. The population of this study was adolescence who lives in Bandung orphanages. Respondents in this study were 70 adolescents aged 15-17 using purposive sampling technique. Two-stage clusters method used for determining the sample of the orphanage. The scales used in this study are Multidimensional Scale of Perceived Social Support (MSPSS), Brief-COPE), and 14-item Resilience Scale (RS-14). Respondents filled out the questionnaires with a paper and pencil test in their orphanages. The data analysis using descriptive analysis and multiple regression analysis. The results of data analysis showed that perceived social support and problem-focused coping together affect resilience of 41% with the strength of the relationship at moderate level. The regression coefficient values for perceived social support variable (4,051) and problem-focused coping variable (1,162). This showed that perceived social support more influence than problem-focused coping on adolescence resilience.